Assessment of equilibrium field coil misalignments on the divertor footprints in NSTX-U. (12th June 2019) - Munaretto, S.; Evans, T.E.; Ferraro, N.M.; Orlov, D.M.; Trevisan, G.L.; Wu, W.
Abstract: The presence of error fields in a tokamak device is inevitable, so it is of fundamental importance to understand their impact on the operation of the device and up to what level they can be tolerated. In this paper a prediction of the impact on the magnetic footprints on the divertor plates due to the misalignment of NSTX-U equilibrium coils is presented. Resistive MHD simulations are used to predict the magnetic field perturbations experienced by the field lines due to the presence of error fields. A linear relation between the magnitude of the misalignment and the area of the magnetic footprints is found, as well as an inverse proportionality between the size of a magnetic footprint and the plasma penetration of the field lines composing the footprint. This study is intended as a starting point in the process of investigating divertor footprints associated with the plasma response to intrinsic error fields with resistive MHD codes. A basic interpretation of the results suggests that large footprints resulting from equilibrium coils misalignment may be desirable, to some extent, to decrease the peak heat load on the divertor components. A more complete interpretation of the results presented here will involve a number of complex physics issues, for example pedestal transport and stability, along with the role of various scrape-off layer and divertor processes, as well as experimental data to confirm the predictions.